The Philosophy of Brentano : Contributions from the Second International Conference Graz 1977-2017. In memory of Rudolf Haller - Antonelli, Mauro,; Binder, Thomas, (Studien zur Österreichischen Philosophie ;, 2021)
This volume, originating from the centennial Second International Conference Graz 1977-2017 on Franz Brentano's philosophy, collects eighteen essays written by nineteen distinguished specialists covering the main areas of Brentano's philosophy: his epistemology, ontology, ethics, and logic, and his contributions to psychology and philosophy of mind. Its goal is to explore the significance and impact of Brentano's thought, to promote a deepening of the ongoing renaissance of interest in Brentano, and to advance the project of understanding Brentano's actual philosophical positions and correcting entrenched misunderstandings.